2020
DOI: 10.1177/0269216320967547
|View full text |Cite
|
Sign up to set email alerts
|

Home or hospital as the place of end-of-life care and death: A grounded theory study of parents’ decision-making

Abstract: Background: While several studies have examined ‘what’ families want with regard to the place of a child’s end-of-life care and death, few have explored ‘how’ parents reach a decision. Aims: (1) to develop a model explaining how parents of a child with a life-threatening illness in Greece decide about the place of end-of-life care and death; (2) to identify the factors affecting decision-making; (3) to consider the implications for clinical practice. Design: Grounded theory study of bereaved parents using semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…20 Qualitative data were collected through a single open-ended question included in the questionnaire asking, "If you didn't feel prepared for the kind of medical and emotional problems the child experienced at endof-life phase, what would have been helpful?" 20 A variety of qualitative methods were used to analyze data, including grounded theory analysis, 26,28,29,31 thematic analysis, 19,20,24,25,30 content analysis, 17,18,21 phenomenology, 22,33 and use of a conceptual analytical framework. 23 Management of data was consistent across studies, with all reporting audio recording of interviews and transcription of interviews verbatim.…”
Section: Methods Of Data Collection and Analysis For Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Qualitative data were collected through a single open-ended question included in the questionnaire asking, "If you didn't feel prepared for the kind of medical and emotional problems the child experienced at endof-life phase, what would have been helpful?" 20 A variety of qualitative methods were used to analyze data, including grounded theory analysis, 26,28,29,31 thematic analysis, 19,20,24,25,30 content analysis, 17,18,21 phenomenology, 22,33 and use of a conceptual analytical framework. 23 Management of data was consistent across studies, with all reporting audio recording of interviews and transcription of interviews verbatim.…”
Section: Methods Of Data Collection and Analysis For Included Studiesmentioning
confidence: 99%
“…One study included data on adolescents and young adults aged 15-25 years, as over half represented adolescents were aged 15-18 years, the relevant data from this study was included. 30 Three studies 23,29,31 included parents of children with malignant and nonmalignant conditions and only qualitative data from children who died from cancer were extracted and synthesized.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications often need highly specialized cure-focused care, including PICU, [6,8] suggesting less predictable pathways. Qualitative research involving bereaved parents identified several factors that affect parents when deciding on the place of EOL care, among others, awareness of the child's dying and timing of the decision-making [9]. Since the EOL care-pathway is difficult to predict, especially in the case of HSCT-related complications, the timing and opportunity of EOL decision-making may come too late or may easily be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, three showed that pediatric HSCT patients often died from treatment-related complications (60, 68, and 81%) compared to disease-related (40, 32, and 19%) [4,6,8]. The place of death of a child with an incurable illness depends on several factors [9] and varies in several studies [10,11]. In the USA between 1989-2003, the place of death for children whose deaths were attributed to complex chronic conditions increasingly shifted from predominantly hospital to home setting [10].…”
Section: Introductionmentioning
confidence: 99%